Managing linguistic diversity in literacy and language development : an analysis of teachers' attitudes, skills and strategies in multilingual Kenyan primary school classrooms - Nyaga, Susan Karigu (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.